2017
DOI: 10.3171/2016.7.spine16172
|View full text |Cite
|
Sign up to set email alerts
|

Posterior corrective surgery with a multilevel transforaminal lumbar interbody fusion and a rod rotation maneuver for patients with degenerative lumbar kyphoscoliosis

Abstract: The purpose of this study was to assess the clinical results of posterior corrective surgery using a multilevel transforaminal lumbar interbody fusion (TLIF) with a rod rotation (RR) and to evaluate the segmental corrective effect of a TLIF using CT imaging. The medical records of 15 consecutive patients with degenerative lumbar kyphoscoliosis (DLKS) who had undergone posterior spinal corrective surgery using a multilevel TLIF with an RR technique and who had a minimum follow-up of 2 years were retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
1
17
2
Order By: Relevance
“…Thus, it should be emphasized that examination of ESR and CRP level and application of anti-inflammation medication should be regularly performed for AS patients without fully ossified bridging syndesmophytes during the follow-up period to prevent the loss of correction [ 23 , 24 ]. Nevertheless, the above-mentioned results were not completely in accordance with the conclusions reported by several previous studies in adult spinal deformity (ASD) [ 9 11 ]. In a study of 183 ASD patients reported by Theologis et al [ 11 ], the instrumented lumbar levels were assumed to be the primary cause for loss of lumbar sagittal correction in long adult deformity constructs.…”
Section: Discussioncontrasting
confidence: 71%
“…Thus, it should be emphasized that examination of ESR and CRP level and application of anti-inflammation medication should be regularly performed for AS patients without fully ossified bridging syndesmophytes during the follow-up period to prevent the loss of correction [ 23 , 24 ]. Nevertheless, the above-mentioned results were not completely in accordance with the conclusions reported by several previous studies in adult spinal deformity (ASD) [ 9 11 ]. In a study of 183 ASD patients reported by Theologis et al [ 11 ], the instrumented lumbar levels were assumed to be the primary cause for loss of lumbar sagittal correction in long adult deformity constructs.…”
Section: Discussioncontrasting
confidence: 71%
“…Coronal horizontalization of L4 reflects the magnitude of correction in fractional curve, it is of great importance during correction of coronal imbalance in patients with coronal consistency pattern, which can provide a leveled foundation to facilitate the correction of the curve(s) above L4. Posterior column osteotomy in the lumbosacral fractional curve plus TLIFs (L5S1, L4/5) could provide effective correction to achieve the coronal horizontalization of L4 15 . On the other hand, in patients with coronal opposition pattern, coronal horizontalization of L4 does not seem as critical as in patients with coronal consistency pattern.…”
Section: Discussionmentioning
confidence: 99%
“…However, in other disorders such as fractures or spondylolisthesis, where minimally invasive surgery is used as the means of treatment, for these to succeed, it is absolutely necessary that the disc remains healthy. However, disc degeneration is also implicated in the development of spinal pathologies which affect the elderly in particular, such as spinal stenosis[ 50 ] and kyphoscoliosis[ 51 ]. With the increase in numbers of the elderly, and the growing incidence of spinal problems in this population, the results of this study show that more attention needs to be given to factors leading to degenerative changes in the disc, not only in middle age but right throughout life.…”
Section: Discussionmentioning
confidence: 99%